The Case of Ashley Smith: Policy Window or Policy Failure? - Onishenko, Dawn; Erbland, Julie (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
On December 19, 2013, six years after the death of Ashley Smith in an Ontario women’s correctional facility, a Coroner’s Jury determined that the death of Ashley Smith was a homicide. Using policy theory related to focusing events, policy windows, problem definition and policy communities, this article reflects on the circumstances surrounding the death of Ashley Smith. It considers whether this event has created a focus on the issues pertaining to the criminalization of individuals with mental health issues. Has it acted as a catalyst for policy change, or simply represents a missed opportunity and a tragic symbol of a larger systemic policy failure? Ultimately, this article speculates on how tragic events such as this can be identified as policy windows and leveraged for social change. Keywords: Criminalization; mental health; Intersectionality; gender Résumé Le 19 décembre 2013, six ans après la mort d'Ashley Smith dans une prison pour femmes en Ontario, le jury du coroner déterminait que la mort d'Ashley Smith était un homicide. Cet article examine les circonstances entourant la mort d'Ashley Smith, utilisant des concepts de théorie de politique, comme évènement marquant, une occasion d'influer sur les politiques, la définition du problème, et une communauté politique. Est-ce que cet évènement a rendu possible la considération des problématiques issues de la criminalisation des personnes ayant des problèmes de santé mentale? As-t-il agit come un catalyse pour des changements de politique, ou bien, représentes-t-il une opportunité manquée, et un symbole tragique d'un échec de politique dans un contexte systémique plus vaste? Ultimement, cet article s'interrogé sur la possibilité d'évènement tragique comme celui-ci, de servir comme une occasion d'influer sur les politiques sociale et d'effectuer des changements dans celle-ci. Mots-clefs: Criminalisation; santé mentale; analyse intersectionelle; genre